Transarterial Embolization for Hematuria after Percutaneous Nephrolithotomy (PCNL) - Andy Susanto; Stephanus Tangel; Djony Edward Tjandra; Richard Marnix Sumangkut (Rifa'Institute, 2026)
Introduction: Arterial embolization is an effective definitive therapy for treating severe bleeding after percutaneous nephrolithotomy (PCNL), especially when caused by vascular lesions such as pseudoaneurysms. Although rare, this complication can lead to massive hematuria and hemodynamic instability if not promptly treated. Methods: This is a descriptive case report of four patients experiencing post-PCNL bleeding. All patients underwent angiography and selective arterial embolization procedures appropriate to the vascular lesions identified. Results and Discussion: All four patients demonstrated significant clinical improvement after embolization. Angiography demonstrated successful occlusion of the bleeding source, and after approximately four days of observation, the patients clinically experienced no bloody urination and no post-procedure complications. Conclusion: Selective arterial embolization is an effective and safe treatment for massive post-PCNL bleeding due to vascular lesions such as pseudoaneurysms. The success of the procedure depends heavily on early detection, access to angiography facilities, and operator skill. Embolization should be a primary consideration in the management of severe hematuria after PCNL prior to performing invasive procedures